Las tecnologías de la información en América Latina, su incidencia en la productividad: Un análisis comparado con países desarrollados (2017)
The advancement of science in the global context in the last half century has been attributed to high levels of information available online, which were transformed in knowledge, innovation and productivity. Thus, the availability and use of information and communications technology (ICT) has been growing and becoming complex in industrialized countries. This work aimed to perform a comparative analysis of the use of ICT among six countries in Latin America and seven developed countries. Methodologically, the study carried out an analysis of the state of the art of the use of ICT in Latin America, and a theoretical and statistical verification. The results showed strong gaps in technology, knowledge, productivity and innovation in the region. The article concluded and shown as a first evidence that ICT was a causal reason for the low level of productivity and quality of life in Latin America. © The author; licensee Universidad Nacional de Colombia.